Study on optimal dietary crude protein level in Japanese white rabbits from weaning to 80-day old - LÜ Jian-min; SONG Jian-hui; XU Jian-qin; ZHANG Li-zong; LIU Jian-xin (浙江大学学报. 农业与生命科学版, 2008)
A six-week feeding trial was carried out to assess the optimal dietary crude protein level in Japanese white rabbits from weaning to 80-day old. Sixty weanling (40 d old) Japanese white rabbits were divided into 5 groups (Ⅰ, Ⅱ. Ⅲ. Ⅳ and Ⅴ) according to dietary crude protein levels (12%, 14%, 16%, 18% and 20%, respectively). Digestible energy and crude fibre contents of the diets were equal except the crude protein content. The growth performance and feed intake were measured through the experiment. When the trial was finished, the biochemical indices were determined. Results show that crude protein levels had significant effect on daily gain and body weight, with the highest daily gain and body weight at the 16% crude protein level. The activity of alkaline phosphatase (AKP) was the highest in group Ⅲ, but no significant difference was found. The blood serum total protein and albumin in Ⅱ-Ⅴ groups were higher than those in group I. The contents of urea-N were increased with increasing dietary crude protein level, but it was suitable in the third group. In conclusion, the optimal dietary crude protein level of Japanese white rabbits is 16% during growing period.